Separation of dielectric and space charge polarizations in CaCu3Ti4O12/CaTiO3 composite polycrystalline systems - Bueno, Paulo Roberto [UNESP]; Ribeiro, William C.; Ramirez, Miguel A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Institute of Physics (AIP), 2007)
The complex analysis of dielectric/capacitance is a very useful approach to separate different polarization contributions existing in polycrystalline ceramics. In this letter, the authors use this type of spectroscopic analysis to separate the bulk's dielectric dipolar relaxation contributions from the polarization contribution due to space charge in the grain boundaries of a CaCu3Ti4O12/CaTiO3 polycrystalline composite system. The bulk dielectric dipolar relaxation was attributed to the self-intertwined domain structures from the CaCu3Ti4O12 phase coupled to the dipole relaxation from the CaTiO3 phase, while the space charge relaxation was attributed to the Schottky-type potential barrier responsible for the highly non-Ohmic properties observed in this composite polycrystalline system.